STRATEGI PENGEMBANGAN PROFIL PELAJAR RAHMATAN LIL ALAMIN PADA KURIKULUM MERDEKA SEBAGAI UPAYA MENINGKATKAN KARAKTER RELIGIUS SISWA - Sirait, Azyana Alda; Febrian, Agil; Halimah, Siti (Reflektika, 2024)
AbstractIn facing the challenges of globalization, madrasah has an important role in shaping students' religious character. Character education based on the concept of Rahmatan Lil Alamin emphasizes tolerance, compassion, justice, and kindness. This study aims to identify effective strategies in developing the Rahmatan Lil Alamin learner profile in madrasah. After the data were analyzed, the results showed that the Rahmatan Lil Alamin profile emphasizes the formation of students' characters who are religious, responsible, and beneficial to society. Implementation is done through intracurricular, co-curricular, and extracurricular activities with holistic, contextual, student-centered, and inclusive principles. Madrasahs work together with the community to create a supportive environment. The results of the study are expected to make a significant contribution to character education in madrasahs, strengthening their role in forming a generation with religious character and rahmatan lil alamin.